Combined Tide and Storm Influence on Facies Sedimentation of Miocene Miri Formation, Sarawak - Ulfa, Yuniarti; Sapari, Nasiman; Harith, Zuhar Zahir Tuan (EKSPLORIUM, 2011)
This study was conducted on the sedimentary rocks belonging to the Miri Formation (Middle – Late Miocene). The primary objective of the present study is to provide additional interpretation on the stratigraphy of the Miri Formation in the Miri Field based on the new information gathered from new outcrops in the area. Five outcrops were examined in detail on sedimentology and stratigraphy. Based on lithology, sedimentary structures, bedding geometry and traces fossil, the sediments of the Miri Formation were grouped into fourteen lithofacies. Influence of tide and storm during the depositional processes of the formation were indicated by the group of two main facies associations which are: (i) tide-dominated estuary; and (ii) wave-and-storm dominated facies associations. The tide-dominated estuary system of the Miri Formation are includes variety of sub environments: estuary mouth or tidal channel and sand bars (characterized by trough cross-stratified sandstone with mud drapes facies), estuary channel or upper flow regime of sand flat (characterized by parallel stratified sandstone with mud-laminas facies), mixed-tidal flat (characterized by wavy and flaser bedded sandstone facies), and mud-tidal flat (characterized by rhythmic stratified sandstone-mudstone and lenticular bedding facies). The wave-and-storm dominated varied from lower to middle shoreface (characterized by hummocky cross-stratified sandstone and rhythmic parallel stratified sandstone and laminated siltstone facies), upper shoreface (characterized by swaley cross-stratified sandstone), lower shoreface (interbedded to bioturbated sandstone and siltstone facies), and offshore transitional (characterized by bioturbated sandstone and mudstone interbedding with parallel to hummocky cross-stratified sandstone facies).